Analysis of the Impact of Inadequate Nutritional Intake on the Risk of Stunting in Early Childhood in Ngadhamana Village - Helena Rhero Wea; Elisabeth Tantiana Ngura; Angelina Kurnia Juita; Konstantinus Dua Dhiu (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to identify and understand the impact of inadequate nutritional intake on the risk of stunting in early childhood. The urgency of this research lies in examining how insufficient nutritional intake affects the risk of stunting. The research subjects included children aged 0–6 years, parents, community health volunteers (posyandu cadres), and health workers directly involved in monitoring child growth and development. The research employed a qualitative method using interview, observation, and documentation techniques so that researchers could explore detailed information regarding dietary patterns and other factors influencing children's nutritional status. The data analysis technique used consisted of data collection, data reduction, data presentation, and conclusion drawing. The research instruments used were interview guidelines, observation sheets, and recording tools such as notebooks and voice recorders to ensure the accuracy of the collected data. The findings revealed that some early childhood children in Ngadhamana Village had not yet received nutritional intake in accordance with the Recommended Dietary Allowance (RDA), particularly low consumption of animal protein, vegetables, and fruits, accompanied by the habit of consuming instant snacks. This condition has an impact on the inhibition of children's growth.